Corporate entrepreneurship, supply chain management strategies and performance in the setting of Saudi Arabia: Empirical investigation - Khaled Salmen Aljaaidi (Journal of Project Management)
The objective of this study is to assess the joint effect of corporate entrepreneurship (CE) and supply chain management (SCM) strategies on firm performance in the circumstance of Saudi Arabian manufacturing firms. This is interesting in the sense that while previous scholars have focused on CE and SCM separately, the combinative aspect of the two particularly in nonwestern countries seems still to be short of attention. In this respect, this paper attempts to apply a resource-based view and suggest that CE and SCM complement each other and in the end performance of the firm will be increased. Out of the 84 Saudi manufacturing firms covered in the structured survey, data was analyzed using Ordinary Least Squares (OLS) regression. The results indicate that CE, particularly dimensions such as new business venturing, product innovation, technological entrepreneurship, mission reformulation, reorganization and system-wide changes, significantly enhances firm performance. Additionally, SCM strategies were found to have a positive and statistically significant impact on firm performance, highlighting the critical role of effective supply chain management in operational efficiency and competitive positioning. The findings contribute to the literature by providing empirical evidence from a Middle Eastern context, thereby enhancing the generalizability of existing theories on CE and SCM. The study also offers practical implications for managers and policymakers, suggesting that aligning CE initiatives with SCM strategies can drive sustained competitive advantage. These insights are particularly relevant for firms operating in emerging markets, where economic reforms and diversification efforts, such as Saudi Arabia's Vision 2030, necessitate strategic innovation and supply chain optimization.